Skeletal Muscle 31P MR Spectroscopy Surpasses CT in Predicting Patient Survival After Liver Transplantation - Kyselova, Denisa; Mikova, Irena; Sedivy, Petr; Dezortova, Monika; Hajek, Milan; Mares, Jan; Tupy, Marek; Kautznerova, Dana; Kysela, Marek; Fronek, Jiri; Spicak, Julius; Trunecka, Pavel (Journal of cachexia, sarcopenia and muscle, 2025)
BACKGROUND: Skeletal muscle alterations are associated with higher mortality and morbidity in patients with liver cirrhosis. Assessing these changes seems to be a promising method for identifying patients at a high risk of poor outcomes following liver transplantation (LT). This is particularly important given the current global shortage of organ donors. However, evidence of the impact of these alterations on the prognosis of patients undergoing LT is inconclusive. The aim of our prospective study was to evaluate the impact of skeletal muscle changes, reflected in sarcopenia, myosteatosis and metabolic changes in the calf muscles, on perioperative outcomes and long-term survival after LT. We also sought to determine the posttransplant evolution of the resting muscle metabolism. METHODS: We examined 134 adult LT candidates. Of these, 105 underwent LT. Sarcopenia and myosteatosis were diagnosed by measuring the skeletal muscle index and mean psoas muscle radiation attenuation, respectively, which were obtained from computed tomography (CT) scans taken during pretransplant assessment. Additionally, patients underwent 31P MR spectroscopy (MRS) of the calf muscles at rest before LT and 6, 12 and 24 months thereafter. The median follow-up was 6 years. RESULTS: Patients with abnormal 31P MRS results and CT-diagnosed myosteatosis prior to LT had significantly worse long-term survival after LT (hazard ratio (HR), 3.36; 95% confidence interval (CI), 1.48-7.60; p = 0.0021 and HR, 2.58; 95% CI, 1.06-6.29; p = 0.03, respectively). Multivariable analysis showed that abnormal 31P MR spectra (HR, 3.40; 95% CI, 1.50-7.71; p = 0.003) were a better predictor of worse long-term survival after LT than myosteatosis (HR, 2.78; 95% CI, 1.14-6.78; p = 0.025). Patients with abnormal 31P MR spectra had higher blood loss during LT (p = 0.038), required a higher number of red blood cell transfusions (p = 0.006) and stayed longer in ICU (p = 0.041) and hospital (p = 0.007). Myosteatosis was associated with more revision surgeries following LT (p = 0.038) and a higher number of received red blood cell transfusion units (p = 0.002). Sarcopenia had no significant effect on posttransplant patient survival. An improvement in the resting metabolism of the calf muscles was observed at 12 and 24 months after LT. CONCLUSIONS: Abnormal 31P MRS results of calf muscles were superior to CT-based diagnosis of myosteatosis and sarcopenia in predicting perioperative complications and long-term survival after LT. Resting muscle metabolism normalized 1 year after LT in most recipients.
Keywords: počítačová rentgenová tomografie; Humans; lidé středního věku; Female; Aged; dospělí; Sarcopenia; senioři; lidé; magnetická rezonanční spektroskopie; Liver Transplantation; transplantace jater; Adult; kosterní svaly; ženské pohlaví; Male; Middle Aged; Tomography, X-Ray Computed; prognóza; Muscle, Skeletal; sarkopenie; Magnetic Resonance Spectroscopy; mužské pohlaví; prospektivní studie; Prognosis; Prospective Studies